2008
DOI: 10.1159/000113109
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Impregnated Shunt Catheters for the Treatment of Infantile Hydrocephalus

Abstract: Introduction: Antibiotic-impregnated shunt (AIS) components decrease shunt infections by preventing bacterial colonization that occurs during implantation. Despite studies showing improved efficacy in preventing infection however, concern still exists regarding using AIS components in infants, especially premature ones. In this study, clinical outcomes were assessed in infants with hydrocephalus (<1 year) following AIS placement. Methods: A prospective observational study was conducted involving pediatric pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…3,4,22 Within our cohort, there was no significant difference in the rates of VP shunting between temporizing device groups, with 77% of reservoir patients and 76% of VSGS patients eventually receiving VP shunts. In addition, the Cox proportional hazards model found a comparable cumulative incidence of VP shunt placement between the reservoir and VSGS groups.…”
Section: Vp Shunting Ratesmentioning
confidence: 65%
“…3,4,22 Within our cohort, there was no significant difference in the rates of VP shunting between temporizing device groups, with 77% of reservoir patients and 76% of VSGS patients eventually receiving VP shunts. In addition, the Cox proportional hazards model found a comparable cumulative incidence of VP shunt placement between the reservoir and VSGS groups.…”
Section: Vp Shunting Ratesmentioning
confidence: 65%
“…Nineteen full-length papers were reviewed, 13 of which were rejected for the following reasons: studies enrolled either adults only or enrolled mixed populations, but separate results for children were not provided, 1,19,20,36,38,44,45,51 or studies contained patient data that had also been reported in separate publications. 3,16,[47][48][49] In fact, 1 group of researchers published no less than 9 papers on AISs that included patients from overlapping time periods. 3,17,18,35,36,[47][48][49][50] Therefore, 6 articles satisfied inclusion for this systematic review and meta-analysis (Table 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…3,16,[47][48][49] In fact, 1 group of researchers published no less than 9 papers on AISs that included patients from overlapping time periods. 3,17,18,35,36,[47][48][49][50] Therefore, 6 articles satisfied inclusion for this systematic review and meta-analysis (Table 1). 2,15,24,27,28,50 …”
Section: Search Resultsmentioning
confidence: 99%
“…The use of temporizing devices has variable success in reducing shunt placement, as in most studies of reservoirs and VSGSs, the majority of patients go on to permanent shunt insertion [10,29,31,32]. Antibioticimpregnated shunts may be capable of reducing the rates of shunt infection in pediatric hydrocephalus, but do not address the most common cause of shunt failure, proximal obstruction [13,18]. A wide variety of shunt systems are currently available to clinicians, but their impact on shunt failures rates is unclear.…”
Section: Shunt Outcomesmentioning
confidence: 99%